SCUBE3 loss-of-function causes a recognizable recessive developmental disorder due to defective bone morphogenetic protein signaling - Lin, Y-C; Niceta, M; Muto, V; Vona, B; Pagnamenta, AT; Maroofian, R; Beetz, C; van Duyvenvoorde, H; Dentici, ML; Lauffer, P; Vallian, S; Ciolfi, A; et al. (Cell Press, 2020)
Signal peptide-CUB-EGF domain-containing protein 3 (SCUBE3) is a member of a small family of multifunctional cell surface-anchored glycoproteins functioning as co-receptors for a variety of growth factors. Here we report that bi-allelic inactivating variants in SCUBE3 have pleiotropic consequences on development and cause a previously unrecognized syndromic disorder. Eighteen affected individuals from nine unrelated families showed a consistent phenotype characterized by reduced growth, skeletal features, distinctive craniofacial appearance, and dental anomalies. In vitro functional validation studies demonstrated a variable impact of disease-causing variants on transcript processing, protein secretion and function, and their dysregulating effect on bone morphogenetic protein (BMP) signaling. We show that SCUBE3 acts as a BMP2/BMP4 co-receptor, recruits the BMP receptor complexes into raft microdomains, and positively modulates signaling possibly by augmenting the specific interactions between BMPs and BMP type I receptors. Scube3−/− mice showed craniofacial and dental defects, reduced body size, and defective endochondral bone growth due to impaired BMP-mediated chondrogenesis and osteogenesis, recapitulating the human disorder. Our findings identify a human disease caused by defective function of a member of the SCUBE family, and link SCUBE3 to processes controlling growth, morphogenesis, and bone and teeth development through modulation of BMP signaling.